Lasers in the treatment of acne scars. (February 2011) - Choudhary, Sonal; McLeod, Michael; Meshkov, Lauren; Nouri, Keyvan
Acne scars occur as one of the complications of acne vulgaris. A number of therapeutic options are available. Lasers are most useful for grades 2 and 3 acne scars according to the scale put forth by Goodman and colleagues. Nonablative lasers are most appropriate for grade 2 scars, while ablative lasers should be used to treat grade 3 acne scars. Fractional lasers have been developed in an effort to improve the efficacy observed with nonablative lasers, yet reduce the side effects of ablative lasers. Ablative fractional lasers ablate through the epidermis, while nonablative fractional lasers leave the epidermis largely untouched, instead targeting the dermo––epidermal junction. More studies are required to determine the exact placement of fractional lasers in the clinician''s armamentarium.